Treatment-limiting decisions in patients with severe traumatic brain injury in the Netherlands - Inge A.M. van Erp; T.A. van Essen; Erwin J.O. Kompanje; Mathieu van der Jagt; Wouter A. Moojen; Wilco C. Peul; Jeroen T.J.M. van Dijck (Brain and Spine)
Introduction: Treatment-limiting decisions (TLDs) can be inevitable severe traumatic brain injury (s-TBI) patients, but data on their use remain scarce. Research question: To investigate the prevalence, timing and considerations of TLDs in s-TBI patients. Material and methods: s-TBI patients between 2008 and 2017 were analysed retrospecively. Patient data, timing, location, involvement of proxies, and reasons for TLDs were collected. Baseline characteristics and in-hospital outcomes were compared between s-TBI patients with and without TLDs. Results: TLDs were reported in 117 of 270 s-TBI patients (43.3%) and 95.9% of deaths after s-TBI were preceded by a TLD. The majority of TLDs (68.4%) were categorized as withdrawal of therapy, of which withdrawal of organ-support in 64.1%. Neurosurgical intervention was withheld in 29.9%. The median time from admission to TLD was 2 days [IQR, 0–8] and 50.4% of TLDs were made within 3 days of admission. The main reason for a TLD was that the patients were perceived as unsalvageable (66.7%). Nearly all decisions were made multidisciplinary (99.1%) with proxies involvement (75.2%). The predicted mortality (CRASH-score) between patients with and without TLDs were 72.6 vs. 70.6%. The percentage of TLDs in s-TBI patients increased from 20.0% in 2008 to 42.9% in 2012 and 64.3% in 2017. Discussion and conclusion: TLDs occurred in almost half of s-TBI patients and were instituted more frequently over time. Half of TLDs were made within 3 days of admission in spite of baseline prognosis between groups being similar. Future research should address whether prognostic nihilism contributes to self-fulfilling prophecies.